Evaluation of Antimicrobial Activity of Some Mosses From Turkey - DULGER, BASARAN; HACIOGLU, NURCIHAN; UYAR, GURAY (Asian Journal of Chemistry, 2010)
Ethanolic extracts obtained from 5 Byrophyte species (Platyhypnidium riparioides (Hedw.) Dixon, Anomodon viticulosis (Hedw.) Hook & Taylor, Polytrichostrum formosum (Hedw.) G.L.Sm., Plasteurhynchium meridionale (Schimp.) M. Fleish. and Ctenidium molluscum (Hedw.) Mitt. were tested against Bacillus cereus, Bacillus subtilis, Micrococcus luteus, Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Enterobacter aerogenes, Proteus vulgaris, Proteus mirabilis, Pseudomonas aeruginosa, Pseudomonas putida, Salmonella typhimurium, Salmonella typhi, Neisseria gonorhoeae, Candida albicans, Rhodotorula rubra, Kluyveromyces fragilis, Kluyveromyces marxianus and Debaryomyces hansenii by disc diffusion method. The extracts of the plants especially P. meridionale and A. viticulosis were active on all tested microorganisms.